The molecular selectivity of UNC3866 inhibitor for Polycomb CBX7 protein from molecular dynamics simulation. (June 2018) - Liu, Hui; Li, Zhuoming; Li, Liang
Graphical abstract: In this study, we performed two pairs of microsecond molecular dynamic simulations (CBX2 (-UNC3866)) and (CBX7 (-UNC3866)) to study the inhibition and isoform-selective mechanism of UNC3866 to CBX7. Highlights: The comparison of conformational changes of apo- and holo- CBX2 and CBX7 indicates that the aromatic cage of apo-CBX7 protein is more prone to be induced by UNC3866 relative to apo-CBX2 protein. The binding free energy of UNC3866 with CBX7 was lower than that with CBX2, indicating the stronger binding affinity of inhibitor with the former. Asn47 of CBX2 forms a hydrogen bond with the OH group of C-terminal cap of this inhibitor, inducing the conformational changes of diethyllysine of UNC3866 obviously different from that in CBX7. His39 in CBX2 chromodomain interrupts the structured aromatic cage, which partly explains why UNC3866 prefers for binding to CBX7. Abstract: Polycomb CBX proteins regulate gene expression by targeting Polycomb repressive complex 1 (PRC1) to sites of H3K27me3 via their chromodomains, which plays a key role in the development of numerous cancers. UNC3866, is a recently reported peptide-based inhibitor of the methyllysine (Kme) reading function of CBX chromodomains (CBX2, 4 and 6–8). The previous experiments showed that UNC3866 bound the chromodomains of CBX7 strongly, with ∼20-fold selectivity over other CBX chromodomains. However, the potential mechanism of UNC3866 preferentially binding to CBX7 is still unknown. In this study, we performed two pairs of microsecond molecular dynamic simulations (CBX2 (-UNC3866)) and (CBX7 (-UNC3866)) to study the inhibition and isoform-selective mechanism of UNC3866 to CBX7. The conformational analysis of apo- and holo- CBX2 and CBX7 indicated that the aromatic cage of CBX7 protein was more prone to be induced by UNC3866 relative to CBX2 protein. The results of predicted binding free energy suggested the binding affinity of UNC3866 with CBX7 was stronger than that with CBX2, because of the lower binding free energy of the former. Furthermore, the energetic origin of UNC3866 selective for CBX7 protein mainly came from the higher van der Waals contributions. The binding mode analysis showed that Asn47 of CBX2 formed a hydrogen bond with the OH group of C-terminal cap of UNC3866, inducing the conformational changes of diethyllysine of UNC3866 that is obviously different from that in CBX7. Additionally, His39 in CBX2 chromodomain interrupted the structured aromatic cage, partly explaining the reason for UNC3866 preferring for binding to CBX7. The proposal of this selective mechanism could be helpful for the rational design of novel selective inhibitors of the Polycomb CBX protein.